The Role of Socioeconomic Factors and Nutritional Intake in the Nutritional Status of Infants During the First 1,000 Days of Life - Yuliwati Yuliwati; Roichatul Djannah; Rd. Deden Gumilar (Media of Health Research, 2026)
Infants aged 6–24 months are vulnerable to nutritional problems due to the transition from breastfeeding to complementary feeding. Socioeconomic conditions and nutritional fulfillment practices may influence infant nutritional status during this critical growth period. To analyze the relationship between socioeconomic status and nutritional fulfillment practices and the nutritional status of infants aged 6–24 months during the first 1,000 days of life (HPK). A quantitative cross-sectional study was conducted in Taban Village, Jambe Subdistrict, Tangerang Regency, from June to July 2021. The study sample consisted of 127 respondents selected using purposive sampling. Data analysis used the Chi-Square test and logistic regression. Socioeconomic status was associated with infant nutritional status (p=0.014), as were nutritional fulfillment practices (p=0.050). Multivariate analysis identified socioeconomic status (OR=6.31; 95% CI: 1.371–29.041) and nutritional fulfillment practices (OR=5.842; 95% CI: 1.239–27.548) as important factors associated with infant nutritional status. Socioeconomic status and nutritional fulfillment practices were associated with infants' nutritional status aged 6–24 months. Preventing nutritional problems among infants should involve strengthening families' socioeconomic conditions and promoting balanced complementary feeding practices during early childhood.